Dependence structure of and co-movement between thai currency and international currencies after introduction of quantitative easing - Pathairat Pastpipatkul (2018)
© Springer International Publishing Switzerland 2016. We analyze the dependence relationship between the Thai currency and international currencies after the introduction of quantitative easing (QE). The daily currency exchange rates of Thailand, European countries, Great Britain, Japan, Indonesia, the Philippines, Singapore, and Malaysia during 2009–2014 are applied in this study. We proposed a Markov-switching dynamic copula approach to test the co-movement between the exchange rates and the Thai Baht. The results show that there is a dependence relationship between the Thai Baht and the other currencies except in the case of the Great British Pound. Additionally, we also found that a high dependence regime has higher volatility than a low dependence regime.